DEVELOPMENT OF WULING CAR SALES INFORMATION SYSTEM IN AMBON TO IMPROVE BUSINESS PROCESS EFFICIENCY - Loppies, Adiatma Zefanya (Universitas Multi Data Palembang, 2024)
Wuling car dealer is one of the automotive companies that wants its customers to know that the sales and service process of Wuling cars runs efficiently. To support the best service, changes and improvements in sales and information management related to the car sales process are needed. the development of management information systems is very helpful to answer all the needs needed by the company. The development of an information system for wuling car sales in Ambon will be designed and implemented to help improve the efficiency of the company using the FP-Growth algorithm that will analyze behavior and be able to provide recommendations for wuling products with high success.